Pengabdian Masyarakat dengan Pemanfaatan Limbah Kulit Jagung dalam Pelatihan Kerajinan Tangan pada Masyarakat Desa Parunggalih Pemalang - Hayu Naila Nadzifa; Anggi Herawati Putri; Muhammad Ladzidzur Rizqi; Nur Malisa; Rizqi Mursalina; Anindya Aryu Inayati (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
Located in Bodeh District, Pemalang Regency, Parunggalih Village is a village that is famous for its natural assets in the form of corn. This community service aims to channel new innovations from corn husks and to see the impact it has on the economy and the environment in related areas. The research method used is qualitative research using an observational approach using interview techniques conducted with Parunggalih villagers and an additional approach using the ABCD method to see the economic potential that can be generated from corn husk crafts which include inculturation, discovery, design, and define. The results of the dedication show that corn husk waste can be utilized into various crafts with beautiful aesthetic value and can have a sale value by being marketed and for more effective and efficient digital marketing chosen as a medium for marketing handicraft products from corn husk waste.